Factors Associated With Uptake of Iron Supplement During Pregnancy Among Women of Reproductive Age in Tanzania: an Analysis of Data From the 2015 to 2016 Tanzania Demographic and Health Survey and Malaria Indicators Survey - Moshi, Fabiola Vincent; Millanzi, Walter C.; Mwampagatwa, Ipyana (Frontiers in Public Health, 2021)
Background: Pregnant women are vulnerable to iron deficiency due to more iron is needed primarily to supply the growing fetus and placenta and to increase the maternal red cell mass. Little is known on the factors associated with uptake of iron supplement during pregnancy. Method: The study used data from the 2015-16 Tanzania Demographic and Health Survey and Malaria Indicators Survey (2015-16 TDHS-MIS). A total of 6924 women of active reproductive age from 15 to 49 were included in the analysis. Both univariate and multiple regression analyses were used to determine the association between early antenatal booking and maternal services utilization. Results: Majority of interviewed women 5648(81.6%) ever took iron supplement during pregnancy while a total of 1276(18.4%) women never took iron supplement during pregnancy. After controlling for confounders, predictors for uptake of iron supplement during pregnancy were early antenatal booking (AOR=1.603 at 95% CI=1.362-1.887, p<0.001); rural residence (AOR=0.711 at 95% CI=0.159-0.526, p=0.007); wealth index [rich AOR=1.188 at 95% CI=0.986-1.432, p=0.07)] poor being the reference population; level of education [primary education (AOR=1.187 at 95%CI=1.013-1.391,p=0.034)] no formal education was the reference population; parity [para 2 to 4 (AOR=0.807 at 95%CI=0.668-0.974, p=0.026), para 5 and above (AOR=0.75 at 95%CI=0.592-0.95, p=0.017)] para one was the reference population and zones [ Mainland rural (AOR=0.593 at 95% CI=0.389-0.905, p=0.015), Unguja Island AOR= 0.63 at 95%CI=0.431-0.92,p=0.017] Mainland urban was the reference population and current working status [working (AOR=0.807 at 95% CI=0.687-0.949, p=0.009)] Conclusion: The study revealed that despite of the free access to iron supplement during pregnancy there are women who fail to access the supplement at least once throughout pregnancy. The likelihood to fail to access iron supplement during pregnancy were among pregnant women who initiated antenatal visits late, were from poor families, had no formal education, residing in rural settings, had high parity, were from Mainland rural and were in working status. Interventional studies are recommended in order to come up with effective strategies to increase uptake of iron supplement during pregnancy.